Liga Narodów w polityce zagranicznej Eduarda Beneša (1919-1925) - Nowinowski, Sławomir M. (Acta Universitatis Lodziensis. Folia Historica, 1995)
The future of Czechoslovakia was strictly connected with the Versailles order and mainly with the League of Nations. E. Beneś, who had the greatest influence on the character and activity of the czechoslovakian diplomacy, was greatly attached to the principles of the League of Nations. He described this diplomacy as the vector of his own foreign policy. Apart of his propaganda declarations he demonstrated his activity in the works of the League of Nations. E. Beneś was mainly interested in the most important problems of the First Republic of Czechoslovakia. He took part in the works of realization the idea of common security: the Self-help Treaty and the Geneva Protocol. He wanted to eliminate the procedural precedents, to define the aim and character of the national minority defence. His activity was strictly connected with czechoslovakian foreign policy including the bilateral relations. The vision of the economic sanitation of Austria moved away the danger of Anschluss. And the Petite Entente was a kind of mixed czechoslovakian wants in the Middle Europe and her conceptions as the results of the League Treaty. Beneś was attacked for his free attitude to the obligations of Versailles system and mainly to the League of Nations. Meanwhile it was the League who helped him to become an european diplomat. His presence during many discourses concerning the main problems of Europe let him possess a great influence in the international policy. As a kind of a paradox, such a small country as it was Czechoslovakia had a great international influence. She gained many profits, but they were only temporal.